Cultivating a “Dissenting Frame of Mind”: Radical Education, the Rhetoric of Inquiry, and Anna Barbauld’s Poetry - Sullivan, Brad (Romanticism on the Net, 2007)
AbstractTrue to her origins in a prominent Dissenting family, Anna Aikin Barbauld was cautious in her appraisal of existing (and often oppressive) authority structures. Her work is underscored by her understanding that established power structures are incomplete, sometimes incoherent, and usually dangerous to those that attempt to subvert them. Her poetry shows a sophisticated awareness of hierarchy as a frame of mind that needs to be disrupted and re-modeled, as a poor mental construct that pervades much of our thinking about social roles, gender, and—of course—religious practice. But rather than choosing the path of radicalism and radical idealism, Barbauld accepted the fact that realities do not always respond quickly to new critical understandings. Her poetry engages us in experiences that provoke questions and encourage further inquiry—that seek to establish what might be called a “Dissenting frame of mind.” By juxtaposing the languages of science and nurture, and by transforming ordinary experiences into extraordinary ones, Barbauld disrupts reader expectations and provokes re-evaluation of assumptions, prejudices, and “the normal.” The key to change, for Barbauld, is the ability to “think again.” And her poetry is crafted to help readers do just that.